Clinically relevant biomarkers in acute heart failure: an update - Mukherji, Agnibh; Ansari, Uzair; Borggrefe, Martin; Akın, Ibrahim; Behnes, Michael (Current pharmaceutical biotechnology, 2017)
Background: Acute Heart Failure (AHF), owing to the difficulties in diagnosis, prognostic stratification and patient-related management, is still associated with unusually high morbidity and mortality. The advent of novel biomarkers apart from natriuretic peptides involved in myocardial injury, neuro-hormonal activation, and ventricular remodeling augurs immense hope in redefining the biomarker-based approach towards AHF. Methods: A thorough review of the available literature including latest review articles from distinguished experts, textbook references and guidelines from leading cardiological societies worldwide as well as the latest trials, encompassing various biomarkers known in AHF was conducted. The most relevant ones were chosen as references for the current review article. Results: Biomarkers such as midregional proatrial natriuretic peptide, soluble ST2, highly-sensitive troponin, and midregional proadrenomedullin are some such examples that have passed various stages of substantiation while there is an array of potential biomarkers innascent stages like osteopontin, CTGF, GDF-15 and TGF beta-1 awaiting further reiteration. Not only the diagnosis of AHF itself but the evaluation of co-morbidities using markers like PCT, hematologic markers or acute kidney injury markers like NGAL present a new perspective to the management of AHF. Conclusion: This review article outlines the current status of the most relevant cardiac biomarkers related to AHF.
Gesehen am 25.04.2018